Profil Berpikir Fungsional Siswa SMP dalam Menyelesaikan Masalah Matematika Ditinjau dari Perbedaan Jenis Kelamin - Siregar, Ardianto Pandapotan; Juniati, Dwi; Sulaiman, Raden (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2017)
This research was conducted at 2 students of SMPK Anak Bangsa Surabaya grade VIII. Subjects were selected based on the basic of equal mathematics ability. Data was collected using provision of problem-solving and task-based interview. Data was analysed using data reduction steps, data presentation, and conclusions. Meanwhile, to obtain valid research data in this study, researchers used time triangulation. The results indicated that in the number 1 problem of identifying patterns, the subjects of men and women tend to have similarities in stating what is known and asked the question, but the male students are more specific to explain the magnitude of the difference between the first quantity Followed by increased differences in other quantities. Related activities determine the relationship between two quantities, male subjects and women subject tend to have similarities in how to determine the relationship between two quantities that is by trial and error using existing mathematical operations.It can be concluded that the functional way of thinking both subjects is relatively the same. Its just that the male subject is more specific in finding the difference between the two quantities and finding the correspondence relationship between the quantities